Perception and Acceptability of Regular Education Teachers Towards Inclusion of Children with Intellectual Disability in Calabar, Cross River State, Nigeria - Akinwumi, Aderibigbe Samson; Philip, Adeleke Owoade; Ayorinde, Akintoye Oluyemi; Ajah, Mabel Obioma; Emmanuel, Ahuenasebhor; Sade, Okoye Joy; Osa, Igbineweka Paul; Etukudo, Ogunjimi Blessing; Ayibeya, Apie Martina; Ongbonya, Ntino Martina; Inyang, Okoi Ikpi; Okorn, Obeten Okoi; et al. (Journal of Intellectual Disability - Diagnosis and Treatment, 2024)
Access to education has been a challenge to individuals with intellectual disability (ID) in Cross River State, Nigeria, as a result of limited schools that accept these individuals. This study consequently investigated the knowledge and perception of regular teachers about children with ID and their level of acceptance into the regular classroom. Two hundred (200) teachers in public primary schools in Calabar municipal were randomly selected for the study. A descriptive research design was adopted. “Teachers’ Knowledge, Perception and Acceptability of Teachers towards Children with Intellectual Disability (TKPATCID)” was used as an instrument for data collection. Data was analyzed using descriptive statistics such as frequency count, simple percentage standard deviation, and mean scores. Findings showed that the knowledge of regular teachers about children with ID is very low. The majority of the regular teachers have negative perceptions of children with ID. Similarly, the majority of the respondents were of the opinion that children with ID should not be accepted alongside their non-disabled counterparts in the classroom. It was therefore recommended, among others, that awareness of the nature of ID be created. Regular in-service training should be organized for regular education teachers by the government in order to properly equip them with relevant and up-to-date knowledge of children with ID.